2017
DOI: 10.1007/s40262-017-0546-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Clinical Pharmacokinetics, Pharmacodynamics, and Immunogenicity of Vedolizumab

Abstract: Vedolizumab is a humanized anti-α4β7 integrin monoclonal antibody that selectively blocks trafficking of memory T cells to inflamed gut tissue by inhibiting the α4β7-mucosal addressin cell adhesion molecule-1 (MAdCAM-1) interaction. Approved for treating patients with moderately to severely active ulcerative colitis (UC) or Crohn’s disease (CD), vedolizumab is administered as a 300 mg intravenous infusion. Vedolizumab undergoes a rapid, saturable, non-linear, target-mediated elimination process at low concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 46 publications
9
101
1
2
Order By: Relevance
“…From these, 32 studies focusing on vedolizumab were identified for full text review, and five studies were included in quantitative synthesis (Figure ) . Additionally, data from five studies was qualitatively synthesized to inform vedolizumab concentrations associated with favourable outcomes . Multiple studies were reported using the GEMINI trials and unique aspects of each analyses were used to quantitatively or qualitatively inform evidence on role of TDM with vedolizumab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these, 32 studies focusing on vedolizumab were identified for full text review, and five studies were included in quantitative synthesis (Figure ) . Additionally, data from five studies was qualitatively synthesized to inform vedolizumab concentrations associated with favourable outcomes . Multiple studies were reported using the GEMINI trials and unique aspects of each analyses were used to quantitatively or qualitatively inform evidence on role of TDM with vedolizumab.…”
Section: Resultsmentioning
confidence: 99%
“…It is unclear whether “subtherapeutic” vedolizumab concentration (below these thresholds) is a consequence of rapid drug clearance or the cause of inadequate response. Mechanistically, unlike cytokine antagonists, vedolizumab binds to the α 4 β 7 integrin and blocks lymphocyte interaction with mucosal addressin cell adhesion molecule‐1 expressed on the endothelium of mesenteric lymph nodes and gastrointestinal mucosa, impairing the migration of gut‐homing lymphocytes into gastrointestinal mucosa . Recent studies have suggested that vedolizumab may exert it's clinical effect through additional mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…This medication is also FDA approved for UC. 270,271 Infliximab (Remicade, Inflectra, Remsira) is a chimeric Mab (IgG1k) with specificity to TNF-a and is FDA approved for IBD and multiple inflammatory arthritic diseases. This medication allows for steroid-free remission within months of starting therapy.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Overall immunogenicity for vedolizumab appears to be low in comparison with conventional anti‐TNF agents. When patients who received/had not received concomitant immunosuppressant at baseline were compared, the risk of developing anti‐vedolizumab antibody was only marginally lower, 3% versus 4% …”
Section: Vedolizumabmentioning
confidence: 99%
“…As little as 2 mg/kg of vedolizumab is sufficient to saturate most α4β7 integrin receptors. Furthermore, receptor occupancy does not correlate with treatment response . It is unclear if this may be related to other unknown mechanisms of action that may benefit from a higher level of vedolizumab …”
Section: Vedolizumabmentioning
confidence: 99%